Sistem Pendukung Keputusan Kelayakan Kredit Denny Jaya Motor Dengan Metode MFEP (Multi Factor Evaluation Process) Berbasis Web - Syahruly Martin; Atang Susila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Deny Jaya Motor was founded in 2015, Based on the results of interviews conducted by researchers with Deny Jaya Motor owners from year to year there has been an increase in the number of car loan applications, the more applications for cars, the higher the risk of arrears in installment payments. This study aims to create a decision support system that provides quick and standardized decisions, provides a sense of trust in providing creditworthiness, for decisions made by the decision support system. The Multifactor Evaluation Process (MFEP) method is one method that can be used in a decision support system. By using the MFEP method, each predetermined criterion is given a weighting according to its needs. The final result of this application system is that the total weighted value of the prospective customer is worth more than 3. Because this total weight value is used as the basis for the priority value of the prospective customer who can be recommended to get credit or not to get credit.